INFLUENCING FACTORS OF VALUATION MULTIPLES OF COMPANIES - CODĂU, Ciprian (Annales Universitatis Apulensis Series Oeconomica, 2013)
The main objective of this study is to determine the factors that influence the valuation multiples used in the market approach in valuing companies. The analysis takes into account both factors related to the company and the country or stock market on which the company stocks are traded. The database for this research was represented by a total of 1,853 companies listed on various stock markets and the source of information was represented by Infinancials database. They were selected based on criteria related to the availability of information and business sectors to which they belong. Such data base includes 15 specific industry sectors, each sector is divided into two data sets according to the level of development of the countries of origin of the companies. Thus the 1,853 companies in the database were divided into companies from developed countries and companies from developing countries. The independent variables considered in this analysis are: company size (quantified by sales), the inflation rate in the country of origin of the company, country risk for the company's home country and three financial ratios considered representative by the investors in the capital market namely: EBITDA ratio, equity/assets ratio and liquidity quick ratio.